Comparison studies of the receptance matrices of the isotropic homogeneous beam and the axially functionally graded beam carrying concentrated masses. (March 2020) - Nguyen, Khoa Viet; Dao, Thao Thi Bich; Van Cao, Mai
Highlights: Receptance matrices of the uniform beam and FGM beam carrying masses are compared. Influences of masses on receptances of beams are investigated. Influence of the varying of mass density on the receptance of FGM beam is studied. Masses located at peaks of the receptance cause these peaks decrease significantly. Experiments have been conducted to justify the theory. Abstract: This paper presents the comparison between the receptance matrices of the isotropic homogeneous beam and the axially functionally graded beam carrying concentrated masses. The general form of receptance functions of the isotropic homogeneous and axially functionally graded beams carrying concentrated masses is presented. The influences of the concentrated masses and the varying of the material properties along the beam on the receptance matrix are investigated. The numerical calculations show that when there are concentrated masses, the receptance matrices of beams are changed. Especially, when masses are attached at peak positions of the receptance matrices, these peaks will decrease significantly. The "peaks" and "nodes" which are the maxima and minima of receptance move to the concentrated mass positions. Due to the varying of mass density, the peaks in the receptance of the axially functionally graded beam in the heavier side is smaller than that of the isotropic homogeneous beam. Also, the peaks and nodes of receptance of the axially functionally graded beam move to the heavier side in comparison with the isotropic homogeneous beam. The experiments have been carried out to justify the theory.